2021
DOI: 10.3390/diagnostics11071255
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of In-Hospital Cardiac Arrest Using Shallow and Deep Learning

Abstract: Sudden cardiac arrest can leave serious brain damage or lead to death, so it is very important to predict before a cardiac arrest occurs. However, early warning score systems including the National Early Warning Score, are associated with low sensitivity and false positives. We applied shallow and deep learning to predict cardiac arrest to overcome these limitations. We evaluated the performance of the Synthetic Minority Oversampling Technique Ratio. We evaluated the performance using a Decision Tree, a Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
0
9
1
Order By: Relevance
“…We confirmed that the check of the measurement of laboratory data did not train as intended. We only used 8 h of past patient data in the previous study [23]. In this study, we excluded a patient whose laboratory data were not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that the check of the measurement of laboratory data did not train as intended. We only used 8 h of past patient data in the previous study [23]. In this study, we excluded a patient whose laboratory data were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we excluded patients whose albumin, bilirubin, creatinine, platelet, hemoglobin, or white blood cell rates were never measured. In our previous research [23], we used input parameters such as laboratory data and laboratory check variables, but it was not properly considered. Table 1 shows the characteristics of our study population.…”
Section: Methodsmentioning
confidence: 99%
“…This shows that the features of the Cleveland dataset are more vital when compared to Framingham. Figure 3 shows the training and validation loss for best performing algorithm i.e., artificial neural network (ANN) [21][22][23][24]. Since the training loss and validation loss are deviating i.e., their incrementing nature is opposite to each other shows that the algorithm is not overfitting which is a good sign.…”
Section: Algorithmmentioning
confidence: 99%
“…In this paper, we piloted the use of an implementation guide that combines IHCA with vital signs, which have been widely adopted in IHCA assessment [4,21] and play an important role in inpatient deterioration detection. Many health care institutions have developed early warning score systems to identify hospitalized patients that are at risk of deterioration, and in recent years, they have begun to incorporate machine learning-based models into this process.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Vital signs have been an important indicator in many studies [1][2][3]. In recent years, researchers have used these data in studies of predictive models for in-hospital cardiac arrest (IHCA) [1,4]. In a real-world medical workflow, complete data may be obtained once every 4 to 8 hours.…”
Section: Introductionmentioning
confidence: 99%